Effect of gelatin on secondary structure, crystallinity and swelling behavior of silk fibroin-gelatin hydrogelsand its application in controlledrelease of nitrogen - Atcharaporn Rattanamanee (2018)
Utilization of natural polymer as biodegradable matrix for the controlled releasingfertilizercan improve the performance of the materials and make them environmentally friendly. In this work, the effect of gelatin on the properties of hydrogels was investigated. The silk fibroin (SF)-gelatin hydrogels were prepared by solvent casting and β-crystallization of SF was promoted via methanol treatment. The secondary structure and the crystallinity of the blended hydrogels wereinvestigatedusing Fourier transform infrared spectroscopy (FT-IR) and X-ray diffraction analysis (XRD), respectively. Moreover, the swelling ratio of the hydrogels and also their kinetics of nitrogen (N) release were also studied.Results from the FT-IR confirmed that no intermolecular interactions had takenplace between SF and gelatin. Furthermore, the increase of gelatin content in the blended hydrogels caused the decrease of the SF crystallinitydetected by XRDwhich corresponded to the swelling behavior of the hydrogel.The release rate of nitrogen (N) depends on the composition of SF and gelatin of which its value of diffusion exponent characteristics (n)determined fromthe Korsmeyer-Peppas model for all of the hydrogels are smaller than 0.5. This indicates that the release of N from the hydrogels isaquasi-Fickian diffusion. Moreover, the release rate (k) and diffusion coefficient (D) of the SF-gelatin hydrogels are lower than those of the SF itself indicating a potential to use the SF-gelatin hydrogel for nitrogen controlled release application. © (2013) Trans Tech Publications, Switzerland.